2021
DOI: 10.1016/j.ejro.2021.100342
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Achilles tendon—A comprehensive pictorial review. Part one

Abstract: Highlights Presence of normal septation between subtendons may mimic an intrasubstance tear. MRI is superior to ultrasound in detection of partial tears. Ultrasound is as useful as MRI in detection of tendinopathy and full-thickness tears. Kager's fat pad is involved in infection more than in postoperative changes. The Achilles tendon xanthoma has a higher signal on T1- and T2-weighted sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…1 Early repair appears as T2 hyperintense signal during the first few weeks that could cause overestimation of the tendon gap superimposed on the physical tendon gap. 5 Fujikawa et al noted a residual tendon gap is sometimes noted postoperatively that was reported to be a normal healing response up to 4 weeks. 1 2 A gap is visualized at 8 weeks on T1 in 10% of open surgical repairs versus 80% in percutaneous repairs that resolved at 12 weeks in both repair techniques.…”
Section: Achilles Treatment Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Early repair appears as T2 hyperintense signal during the first few weeks that could cause overestimation of the tendon gap superimposed on the physical tendon gap. 5 Fujikawa et al noted a residual tendon gap is sometimes noted postoperatively that was reported to be a normal healing response up to 4 weeks. 1 2 A gap is visualized at 8 weeks on T1 in 10% of open surgical repairs versus 80% in percutaneous repairs that resolved at 12 weeks in both repair techniques.…”
Section: Achilles Treatment Techniquesmentioning
confidence: 99%
“…Achilles injury occurs due to chronic overuse in athletes, forceful dorsiflexion, as well as with medications (fluoroquinolones, corticosteroids, oral contraceptives, and hormone replacement therapy), obesity, and inflammatory disorders. 1 2 3 4 5 6 7 8 9 10 11 12 13 14…”
Section: Anatomy and Basic Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography is considered the first-line imaging examination. Xanthomas are visualized as hypoechoic nodules or a diffuse heterogeneous abnormality of the tendon, with markedly increased anteroposterior diameter [ 11 , 12 ]. Surgical treatment of Achilles xanthomas tendon is usually limited to patients who have severe enlargement of the tendon, causing pain or mobility problems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, the tendinopathy grading through MRI has already been discussed in the rotator cuff tendon [ 15 ] and Achilles tendon [ 16 ]. There are few MRI grading studies looking into the degree of CET injury, as described by the combination of various variables such as the gap of tendon, the thickness of tear and the degree of tendinosis [ 17 , 18 ] .…”
Section: Introductionmentioning
confidence: 99%